Histéresis en el desempleo: influencia en la política monetaria del Perú, 1996Q1 – 2017Q4 - García Rieckhof, Diego (2020)
This paper analyzes the dynamics of unemployment and its interaction with the main macroeconomic variables that are considered for monetary policy decisions in Peru. Therefore, unit root tests (with and without structural breakage) are carried out to assess the existence or not of a long-term equilibrium of Peru's unemployment rate. Also, a spectral analysis is performed using the wavelet method coherence to analyze the relationships between the variables in the short, medium and long term. The results of the estimates do no corroborate empirically the hypothesis of the natural rate for unemployment in Peru, but it is not conclusive to prove the presence of hysteresis. Finally, the dynamics of unemployment associated with changes in inflation, the output gap and the GDP decrease rate are not linear and are conditioned by structural changes or multiple balances due to their unitary root characteristics, which may bias the effectiveness of the monetary policy.